The electric power engineering handbook Electric power substations engineering - McDonald, John D. 1951- (CRC Press, 2012)
The use of electric power substations in generation, transmission, and distribution remains one of the most challenging and exciting areas of electric power engineering. Recent technological developments have had a tremendous impact on all aspects of substation design and operation. With 80% of its chapters completely revised and two brand-new chapters on energy storage and Smart Grids, Electric Power Substations Engineering, Third Edition provides an extensive updated overview of substations, serving as a reference and guide for both industry and academia. Contributors have written each chapt.
Previous edition: 2007. - Includes bibliographical references. - Print version record
Keywords: Electric substations; Postes de réseau électrique; electric substations; TECHNOLOGY & ENGINEERING; Electrical